Reasons and solutions for the disconnect between transfusion medicine theory and clinical practice - ZHANG Yinze (Zhongguo shuxue zazhi)
Transfusion medicine, an empirical discipline, evolves through a process of selective retention, where concepts and technologies play a pivotal role. To discern the authentic from the spurious in this knowledge transmission, one must thoroughly understand the historical development of these concepts and technologies, including the contexts and limitations of various conclusions. Crucially, rigorous logical analysis is necessary to identify and address the shortcomings of existing theories. By integrating modern technologies and research findings, we can refine the invaluable insights and conclusions inherited from our predecessors, thereby approximating closer to the true nature of matters. Upon reviewing contemporary theories in transfusion medicine, one finds that some terms, norms, standards, papers and monographs still harbor seemingly plausible yet incorrect concepts and guidelines. This often stems from a lack of understanding of the discipline’s research history, insufficient knowledge accumulation, a deficit in independent and rational thinking, and most importantly, a lack of rigorous logical thought. Through the examples presented in this article, readers are encouraged to appreciate the rational spirit and scientific principles underlying the evolution and process of knowledge. By tracing the developmental trajectory of transfusion medicine, we aim to establish a tightly structured and logically coherent theoretical framework that better serves practical applications and resolves complex issues encountered in the field.